Android Based Sports Infrastructure E-Booking Application at Provincial Youth and Sports Office Using Waterfall Method - Rahma, Firda Aulia; Samsudin (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Booking is an agreement process in the form of ordering goods or services. The Youth and Sports Service (DISPORASU) is a government agency under the auspices of the Governor of North Sumatra. DISPORASU provides sports infrastructure that can be used by the general public by rental method. In the rental process, DISPORASU still applies the direct rental method, by coming to the DISPORASU office in Medan City, so this results in a large number of tenants piling up at the same time. Therefore, a system is needed that helps tenants in carrying out the infrastructure rental process. The concept is an Android-based Sports Infrastructure E-Booking application. This application was built and designed using the waterfall model and UML (Unified Modeling Language) with several diagrams, namely Use Case Diagrams, Activity Diagrams and Class Diagrams. The programming language used is Dart, Flutter Framework and Firebase as the database. By building this sports infrastructure E-Booking application, it is hoped that it can help improve performance in future business processes and become a reference for employees/staff in this agency itself.